Analysis of the Effectiveness of the Animated Video "Siaga Cilik" in Optimizing the Understanding of Flood Disaster Mitigation Concepts in Early Childhood - Dhita Paranita Ningtyas; Dhianne Princesse Ningtyas; Choirudin Choirudin (Journal of Childhood Development, 2026)
This research is motivated by the high risk of flood disasters in the Kampung Melayu Village area, Jatinegara District, East Jakarta, and the low understanding of early childhood about disaster mitigation. The aim of the study was to analyze the effectiveness of the "Siaga Cilik" animated video in optimizing the understanding of flood disaster mitigation concepts in early childhood at PAUD Ruhul Islam Tanah Rendah. The research method used a quantitative approach with a pre-experimental one-group pretest-posttest design. The research subjects were 23 children aged 5-6 years at PAUD Ruhul Islam. The research instrument was an observation sheet on understanding disaster mitigation which included three indicators: knowledge of flood signs, understanding of evacuation actions, and preparedness for facing floods. Data were analyzed using the Wilcoxon Signed Rank Test and N-Gain Score. The results showed a significant increase in children's understanding after the "Siaga Cilik" animated video intervention. The average pretest score of 45.67 (poor category) increased to 82.34 (good category) in the posttest. The Wilcoxon test results showed a p-value = 0.000 < 0.05, which means there is a significant difference between pretest and posttest. The N-Gain Score analysis showed an average value of 0.67 in the medium category. These findings indicate that the "Siaga Cilik" animated video is effective in optimizing the understanding of flood disaster mitigation concepts in early childhood. This research recommends the use of animated media as a disaster mitigation learning strategy that is appropriate to the characteristics of early childhood.